PENGEMBANGAN (R&D) Pengembangan Buku Cerita Digital Bergambar Dalam Pembelajaran PKn Materi Keragaman Agama di Negeriku Pada Siswa Kelas IV SD - Anggelika, Shanda; Romadon; Wahyuningsih, Eka (Universitas Muhammadiyah Bangka Belitung, 2023)
This research was motivated by the lack of use of media so that the learning process carried out by students has not had the maximum effect. This research aims to develop illustrated digital storybooks in learning civics on the material of religious diversity in my country for fourth-grade students as a feasible and practical medium. This study used research and development (R&D) using the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study were fourth-grade students at SD Negeri 38 Pangkalpinang, totalling 39 students. Techniques and data collection instruments in the form of interviews and questionnaires. The data analysis technique was in the form of quantitative descriptive, namely feasibility data carried out by 2 media experts, 1 material expert, and 1 linguist. Practicality data is carried out through teacher responses and student responses. Based on the assessment results obtained from media experts, shows that digital picture storybooks have the criteria of